The Concept of the Unity of Existence in the Intellectual Disposition of Rumi and Leo Tolstoy - Seyede Mohana Seyedaghaie Rezaie (Alzahra University, 2021)
The Unity of Existence is one of the fundamental concepts in theoretical and practical mysticism and in our Islamic-Iranian tradition prominent figures like Ibn Arabi and Rumi have worked on this concept. In his works, Rumi, the great mystic of the seventh century, presents and explicates this concept in different ways, often allegorically. Obviously, this idea is not limited to Islamic-Iranian tradition and traces of these insights could be found in the works of thinkers and writers of other nations. The famous Russian writer and thinker, Leo Tolstoy, has used Oriental wisdoms, rituals, and religions in his spiritual quests for meaning of life. In the meantime, one of the themes permeating all Tolstoy's works, like an invisible thread, is the concept of unity. He discusses unity in a good number of his works including the story of “The Cossacks", the epic novel "War and Peace", "The Death of Ivan Ilyich", his didactic anecdotes, and in the collection "The Way of Life", among others. In this study, we sought to explore the representation of the Unity of Existence in the works of Rumi and Tolstoy. The findings suggest that Tolstoy's allusions to the Unity of Existence could be re-read and examined in light of Rumi's view of the Unity of Existence through a descriptive-comparative approach. In this study, adopting American school in comparative literature approach, we aim to explicate the similarities of views held by Rumi and Tolstoy concerning the Unity of Existence.